Portal de gestión para liquidación de ventas en concesión basada en web service - Asencio, L. (2010)
In this present project it is tried to offer to the Ecuadorian industries a “System of support for the management of sales in concession” that allows through Internet to make a pursuit of given products and to be able to activate the respective collections. That is to say, to have a hall transactional Web and of consultations, that will provide added values to them as saving in time, money and effort. The support tool sets out to be a support in the decision making since it looks for to cover the needs with the industries of the country that they have like commercialization alternative, the sale in consignment or the product delivery in concession, by means of the creation a hall, the use of applicative Web and a Web Service, allowing to share information between suppliers and clients. The solution goes directed to the Ecuadorian manufacturing market, that has seen the sales in consignment like a good opportunity increase its sales or present its new products the final consumer.